Radical Change Accidentally: The Emergence and Amplification of Small Change - Plowman, Donde Ashmos; Baker, Lakami T.; Beck, Tammy E.; Kulkarni, Mukta; Solansky, Stephanie Thomas; Travis, Deandra Villarreal (Academy of Management Journal, 2007)
A decision to offer breakfast to homeless people led to radical change in a church and its environment. Existing theories of change do not fully explain observations from our qualitative study; however, complexity theory constructs suggest how and why such change emerged. We offer four key findings. First, the radical change was unintended, emergent, and slow. Second, destabilizing conditions helped small changes to emerge and become radical. Third, subsequent actions amplified an initial small change and, though not intended to do so, promoted radical change. Finally, the dynamic interaction of amplifying actions, contextual conditions, and small changes led to continuous radical change.